Economic evaluation of five first-line PD-(L)1 inhibitors for treating non-squamous non-small cell lung cancer in China: A cost-effectiveness analysis based on network meta-analysis - Xi Chen; Xi Chen; Mingye Zhao; Mingye Zhao; Lei Tian; Lei Tian (Frontiers Media S.A., 2023)
Background and objective: Non-small cell lung cancer (NSCLC) is one of the most malignant cancer types that causes substantial economic burden in China. This study aimed to evaluate the cost-effectiveness of five first-line anti-PD-(L)1 treatments, including sintilimab, camrelizumab, atezolizumab, pembrolizumab and sugemalimab with each combined with chemotherapy, for treating advanced non-squamous NSCLC (nsq-NSCLC) from Chinese healthcare system perspective.Methods: Clinical data were obtained from the following clinical trials, namely, ORIENT-11, CameL, IMpower132, KEYNOTE-189 and GEMSTONE-302. A network meta-analysis was performed based on fractional polynomial models. We constructed a partitioned survival model with a three-week cycle length and a lifetime horizon to derive the incremental cost-effectiveness ratio (ICER). We performed one-way sensitivity analysis and probablistic sensitivity analysis to test the robustness. Additionally, two scenario analyses were undertaken to investigate the impact of Patient Assistant Program on the economic conclusion and to explore potential uncertainty associated with population representativeness of the global trial.Results: Compared with camrelizumab + chemotherapy, sugemalimab + chemotherapy and atezolizumab + chemotherapy were dominated, and the ICERs generated from sintilimab + chemotherapy and pembrolizumab + chemotherapy were $15,280.83/QALY and $159,784.76/QALY, respectively. Deterministic sensitivity analysis showed that uncertainty around ICERs was mainly driven by HR related parameters derived from NMA and drug price. The probablistic sensitivity analysis suggested that camrelizumab treatment was cost-effective at a willingness-to-pay threshold of 1-time GDP per capita. When the threshold was set as 3-time GDP per capita, sintilimab strategy demonstrated the excellent cost-effective advantage. Sensitivity analysis proved the reliability of base-case results. Results from two scenario analyses indicated that the primary finding was robust.Conclusion: In current context of Chinese healthcare system, sintilimab + chemotherapy appeared to be cost-effective for the treatment of nsq-NSCLC compared with sugemalimab, camrelizumab, pembrolizumab as well as atezolizumab combined with chemotherapy.